Micro-grid reactive power sharing using an adaptive virtual impedance technique - (:unkn) unknown (IEEE, 2019)
The droop control scheme was generally employed in micro-grids (MG), however the main drawbacks of this scheme is its weak performances in reactive power sharing, mainly because of the unequal line impedances. To find a solution of the reactive power sharing inaccuracy, a control methodology based on an adaptive virtual impedance (AVI) is presented. The magnitude drop is adjusted to recompense the low voltage drop in the voltage caused by unequal feeder impedance of distributed generation (DG) units, without using communication links. The scheme of the controller is exposed, analyzed and simulated using MATLAB/SimPowerSystems. Results demonstrated that the adopted methodology can reduce the reactive power sharing error.
Keywords: Micro-Grids; droop control; adaptive vertual impedance; PARALLEL INVERTERS; CONTROLLER